ChemInform Abstract: A Review on Anticancer Potential of Bioactive Heterocycle Quinoline. Issue 32 (August 2015) - Afzal, Obaid; Kumar, Suresh; Haider, Md Rafi; Ali, Md Rahmat; Kumar, Rajiv; Jaggi, Manu; Bawa, Sandhya
Abstract Review: 275 refs.